New records of gastropods from Peruvian littoral - Paredes, Carlos (1998)
Five species of marine gastropods are reported for the first time from Peru: Crepidula nivea Lamarck, 1799, Neosimnia aequalis (Sowerby, 1832), Simnialena rufa (Sowerby, 1832), Nitidiscala elenense (Sowerby, 1844) and Trigonostoma (Ventrilia) bullatum (Sowerby, 1832). Data on habitat and geographical distribution of any one of the species reported is included.